School Environment and Sanitation: A Comparative Study - Anju Damu Ade; Kondagunta Nagaraj; Chandrasekhar Vallepalli (Medsci Publications, 2020)
Background: The health of children and youth is a fundamental value. In many countries there exists a high prevalence of water and sanitation related diseases, causing many people, children in particular, to fall ill or even die. Objectives: The research was undertaken to study the status of school environment and sanitation in urban and rural area of Tirupati; and to compare school environment and sanitation between rural and urban area. Methods: This Cross-sectional study was conducted in Schools of Rural and urban government schools to collect information on various attributes related to school environment and sanitation and were compared between rural and urban schools. Results: School environment and sanitation is suboptimal in both rural and urban government schools. Significantly more urban schools had the infrastructure and sanitation facilities compared to rural government schools.10 (62.5%) schools in rural area had no benches for students. In rural schools 11(68.75%) garbage was disposed by open dumping. Toilet and urinal facility was inadequate and was not separate for boys and girls in some schools. Ventilation was observed to be adequate but natural lightening was not sufficient. Conclusions: Environment and sanitation was found to be slightly better in urban govt. schools than rural government schools.